Democracia e representação: uma apreciação crítica de Carl Schmitt - Cassio Correa Benjamin (2010)
The objective of this work is to accomplish a critique to Carl Schmitts conception about democracy by analyzing two books of his. The first one is Roman Catholicism and Political Form, in which he begins to conceptualize what representation is. However, the main work of our research is the Theory of Constitution. In this book, beyond all discussion about Constitution, the ideas of representation and identity are presented as essential ones for the comprehension of the concept of democracy. In order to achieve our critical analysis on Schmitts position, we commence to consider democracy as self-determination, constituted as procedure by occurring in the scope of immanence. Thus, we have divided the thesis into seven chapters. The first one shows what we understand about democracy and which its basic structure is. As we have already emphasized, the idea of procedure is essential for our definition of democracy. Throughout the following chapters, we examine these both Schmitts books by bringing out the elements that make up a notion of democracy in his thought. In the last chapter, we present a critical appreciation of Schmitts argument from the definition of democracy formerly determinate.